Reflective Teaching: Impact, Supports, and Barriers from UAE-Based ESL Teachers' Perspectives - Sinno, Cherine (2016)
A Master of Arts thesis in Teaching English to Speakers of Other Languages (TESOL) by Cherine Sinno entitled, "Reflective Teaching: Impact, Supports, and Barriers from UAE-Based ESL Teachers' Perspectives," submitted December 2016. Thesis advisor is Dr. Cindy L. Gunn. Soft and hard copy available.